Modeling and Investigation of the Swelling Kinetics of Acrylamide-Sodium Acrylate Hydrogel - Azmi Seyhun Kipcak; Osman Ismail; Ibrahim Doymaz; Sabriye Piskin (Journal of Chemistry)
The acrylamide-sodium acrylate hydrogel was synthesized by free radical polymerization of the method of solution polymerization. Dynamic swelling tests were conducted at 25, 40, and 60°C temperatures, in order to investigate the swelling properties of the synthesized hydrogel. The results have shown that swelling content and swelling rate of the hydrogel increase with increasing the swelling water temperature. The diffusivity values changed from 1.81×10-7 to 2.97×10-7 m2 s−1 over the temperature range. The activation energies were found as 3.56, 3.71, and 3.86 kJ mol−1 at 25, 40, and 60°C, respectively. The experimental drying curves obtained were fitted to a three different models, namely, Peleg’s, first-order absorption kinetic, and exponential association equation models. All the models applied provided a good agreement with the experimental data with high values of the coefficient of determination (R2), the least values of the reduced chi-square (χ2), and root mean square error (RMSE). Comparing the determination of coefficient, reduced chi-square, and root mean square error values of three models, it was concluded that the exponential association equation model represents swelling characteristics better than the others.